Board diversity and total directors’ remuneration: evidence from an emerging market - Abdul Wahab, Effiezal Aswadi; Madah Marzuki, M.; Jaafar, S.; Masron, T. (Emerald Group Publishing, 2018)
This paper aims to examine the relationship between board diversity and total directors ’ remuneration in Malaysia. The authors have operationalised two variables to represent board diversity: the proportion of women directors on the board, to present gender diversity and the proportion of Bumiputras directors, to represent ethnic diversity. Design/methodology/approach – This study has used a panel least squares to test the relationship between board diversity and total directors ’ remuneration. Findings – Based on a 1,094 fi rm-year sample from 2007 to 2009, the authors found a positive and signi fi cant relationship between gender-diverse boards and remuneration, but a negative and signi fi cant relationship between ethnically diverse boards and remuneration. The interaction between gender and ethnically diverse boards results in a weaker negative relationship between ethnically diverse boards and remuneration with an increased presence of women directors. Finally, the authors found a positive and signi fi cant impact on remuneration when there are at least three women and three Bumiputras directors. The fi ndings are robust after controlling for corporate governance variables, institutional variables and fi rm characteristics. Research limitations/implications – The main implication of this fi nding is the positive effect of fi rms hiring more women in top management roles on remuneration. In addition, the negative effect of Bumiputras suggests that their role is to offer political expedience to the board and thus provide economies of scale through their status to the country. Originality/value – This study tests the effect of both gender and ethnicity simultaneously on directors ’ remuneration. Keywords Gender, Ethnicity, Corporate governance, Malaysia, Remuneration, Directors ’ remuneration